Corporate Carbon Footprint Analysis: Example Calculation for a Chemical Factory - Gözde Çolak; Burçin Atılgan Türkmen (Doğal Afetler ve Çevre Dergisi)
In recent years, the concept of sustainable development has emerged as a concept associated with the risk that humanity will be unable to leave a livable world to future generations. The process of sustainable development can move in parallel with advances in economic growth, environmental protection, and social responsibility. Climate change is a major threat to sustainable development, and its effects are becoming more visible as a result of factors such as industrialization, urbanization, and energy consumption. Greenhouse gas emissions must be reduced rapidly in order to mitigate the effects of climate change. The most crucial step in reducing greenhouse gas emissions is to identify the source of the emissions, how they are produced, and the necessary improvement measures. Individual, corporate, and sectoral carbon footprints are calculated for this purpose. The calculation of a company's corporate carbon footprint is frequently the starting point for combating climate change. This calculation identifies the sources of the most greenhouse gases in the enterprise's activities and determines the targets needed to reduce the impact of climate change. This study includes an overview of greenhouse gas emissions, corporate sustainability, corporate carbon footprint and calculation methods, as well as a sample calculation that can be used as a guide by corporate-level carbon footprint calculators.